Sensitizing Young English Language Learners towards Environmental Care (GIST – Education and Learning Research Journal, 2014)
This paper reports an action research study aimed at understanding how to sensitize young English language learners towards caring for the environment. The pedagogical intervention in a 5th grade class consisted in the use of creative writing strategies to express learners’ ideas. Three stages were followed: recognizing facts, reflecting on them and proposing a solution to a problem. The progress learners made at each stage was analyzed. The findings suggest that learners made significant gains in language development and environmental awareness from the opportunities offered by self-expression and debate.
Keywords: Content Based Instruction (CBI); environmental education; environmental raising awareness; sensitizing; young learners; writing